(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
In this article, educational methodical support of specialized subjects was developed. The general and additional requirements for the educational literature of specialized subjects were studied, the main requirements for their structure and content were developed; based on the analysis of the existing educational literature of specialized subjects and the experiences of their development, the additional functions performed by their new generation were determined and the essence of each was clarified.